Green Recovery and Identification of Antioxidant and Enzyme Inhibitor Molecules from Pisco Grape Pomace by Targeted Effects Analysis Using Thin-Layer Chromatography, Bioassay, and Mass Spectrometry - Jacqueline Poblete; Joaquín Fernández-Martínez; Mario Aranda; Issis Quispe-Fuentes (Antioxidants)
The search and identification of inhibitory molecules from novel natural sources, such as pisco grape pomace extract obtained by green techniques, may help to develop agents with therapeutic potential that are beneficial to health with fewer adverse effects than drugs. Many drugs act as enzyme inhibitors, decreasing their activity and thus correcting a metabolic imbalance. This study aims to identify bioactive molecules with antioxidant and inhibitory activity over acetylcholinesterase and cyclooxygenase enzymes present in pisco grape pomace green extracts. Bioactive molecules were detected and identified applying directed effect analysis on planar chromatography coupled to mass spectrometry. For the first time, the presence of antioxidant molecules (quercetin-3-O-glucuronide, quercetin-3-O-glucoside, and gallic acid) and inhibitors of acetylcholinesterase (kaempferol-3-O-glucoside) and cyclooxygenase (gallic acid) enzymes are reported in pisco grape pomace. According to the results, grape pomace could be an alternative to develop novel functional foods and nutraceuticals that provide health benefits and, at the same time, generate a circular economy in the industry.